Comprehensive analysis of the isomiRome in the vegetative organs of the conifer Pinus pinaster under contrasting water availability. (24th December 2020) - Perdiguero, Pedro; Rodrigues, Andreia Santos; Chaves, Inês; Costa, Bruno; Alves, Ana; de María, Nuria; Vélez, María Dolores; Díaz‐Sala, Carmen; Cervera, María Teresa; Miguel, Célia Maria
Abstract: An increasing number of microRNAs (miRNAs) and miRNA‐related sequences produced during miRNA biogenesis, comprising the isomiRome, have been recently highlighted in different species as critical mediators of environmental stress responses. Conifers have some of the largest known genomes but an extensive characterization of the isomiRome from any conifer species has been lacking. We provide here a comprehensive overview of the Pinus pinaster isomiRome expressed in roots, stem and needles under well‐watered and drought conditions. From the 13, 441 unique small RNA sequences identified, 2, 980 were annotated as canonical miRNAs or miRNA* and the remaining were classified as isomiRNA or miRNA‐like sequences. A survey of their expression patterns highlighted roots as the most responsive organ under drought, where specific sequences of which a 24‐nt novel miRNA stood out, were strongly down‐regulated. Given the putative roles of the miRNA‐targeted transcripts validated specifically in root tissues, some of the miRNAs, conserved and novel, are shortlisted as potential regulators of drought response. These results provide a valuable resource for comparative studies between gymnosperms and angiosperms. Furthermore, it evidences high transferability of the isomiRome between pine species being a useful basis for further molecular regulation and physiological studies, and especially those focused on adaptation to drought conditions. Abstract : The present work provides a first characterization of the rich and variable isomiRome encoded by a conifer genome. Results highlight a differential distribution of the isomiRome in different vegetative organs and under contrasting water availability, and potentially targeting transcripts controlling key physiological responses to drought.